2017
DOI: 10.1111/jvim.14845
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Assay for Measuring Canine Platelet Activation and the Inhibitory Effects of Antiplatelet Agents

Abstract: BackgroundAntiplatelet medications are increasingly used in dogs. Remote analysis of platelet activity is challenging, limiting assessment of antiplatelet drug efficacy.Hypothesis/ObjectivesTo evaluate a method used in humans for stimulation and remote analysis of canine platelet activity.AnimalsForty‐five dogs of various ages without a coagulopathy or thrombocytopenia. Six were receiving antiplatelet medication.MethodsProspective observational study. Platelets were stimulated with combinations of arachidonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
(152 reference statements)
3
6
0
Order By: Relevance
“…Although used in multiple human studies, only 1 canine study has described its use 44–48 . This canine study supported the use of Pamfix and found no difference in results for samples stored for up to 22 days 48 . In this current study, the use of Pamfix resulted in no complications or concerns and did not result in increased platelet activation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although used in multiple human studies, only 1 canine study has described its use 44–48 . This canine study supported the use of Pamfix and found no difference in results for samples stored for up to 22 days 48 . In this current study, the use of Pamfix resulted in no complications or concerns and did not result in increased platelet activation.…”
Section: Discussionsupporting
confidence: 63%
“…The current study utilized a fixative solution (Pamfix) designed specifically to fix P‐selectin on activated platelets, thus allowing for delayed flow cytometry analysis. Although used in multiple human studies, only 1 canine study has described its use 44–48 . This canine study supported the use of Pamfix and found no difference in results for samples stored for up to 22 days 48 .…”
Section: Discussionsupporting
confidence: 56%
“…One study assessed whether P-selectin expression could be used to measure platelet function in dogs (44). The relevance is that pets are increasingly given antiplatelet drugs to prevent vascular disease.…”
Section: Veterinary Medicinementioning
confidence: 99%
“…• Expensive equipment has previously limited clinical application as a bedside test. However, a recent study has shown that the addition of a fixative to blood samples may stabilise platelet activation markers for up to 9 days, allowing remote analysis at a central laboratory (Dunning et al 2018). General practitioners are able to request test kits from the company "Platelet Solutions".…”
Section: Tests To Assess Platelet Components and Markers Of Platelet mentioning
confidence: 99%